Synthesis and characterization of silver nanocomposite nanofiltration and forward osmosis membranes based on layer-by-layer assembly - Liu, Xin (2015)
Membrane separation processes, such as nanofiltration (NF) and forward osmosis (FO), have attained great attention and interests due to their various environmental applications including water and wastewater treatment, power generation, seawater desalination, food processing and pharmaceutical industry. However, membrane fouling, especially the irreversible membrane biofouling, remains a major drawback in prolonged membrane operation. The incorporation of bactericidal nanoparticles (NPs), for example silver nanoparticles (AgNPs), in membrane is considered as an effective approach to overcome above obstacle. Layer-by-layer (LbL) assembly method is a promising technique for fabricating different kinds of membranes with versatile structures. This study first investigated the stability and bactericidal activity of AgNPs in environmentally relevant freshwater matrices, and then focused on the development of antimicrobial silver nanocomposite NF and FO membranes based on LbL assembly. Effects of incorporation of AgNPs in membrane substrate on formation of LbL selective layer were also systematically studied. Performances of silver nanocomposite membranes were evaluated and compared with the AgNPs-free controls. The influences of various natural organic matter (NOM) and chelating agent, ethylenediaminetetraacetic acid (EDTA), on AgNPs stability (aggregation, dissolution) and bactericidal activity were investigated by comparing the particle size, surface zeta-potential, and bacterial viability, in terms of half maximal inhibitory concentration (IC50) value, in environmentally relevant freshwater matrices. Bactericidal activity of AgNPs against Bacillus subtilis and Escherichia coli was not substantially affected with the presence of three model NOM, humic acid, bovine serum albumin and alginic acid, at concentration comparable to that of natural freshwaters. Nevertheless, the combined addition of Ca2+ and humic acid induced severe aggregation of AgNPs, resulting in a reduced nanotoxicity. The chelating agent, EDTA, exhibited a concentration-dependent effect on AgNPs bactericidal activity: at low concentration (1 mg/L), EDTA decreased toxicity of AgNPs likely by converting the relatively high toxic dissolved Ag species into a series of low toxic Ag-EDTA complex; at high concentrations (5 and 20 mg/L), EDTA mainly acted as a synergist and increased the toxicity of AgNPs probably by reacting with divalent cations (such as Ca2+ and Mg2+) on bacterial cell membranes. The results not only illustrate the influencing factors of AgNPs toxicity under natural freshwater conditions, but also benefit the understanding of nanotoxicity mechanisms as well as environmental impact assessments of nanomaterials. Novel silver nanocomposite NF and FO membranes were first synthesized by adding the AgNPs in membrane selective layers based on LbL assembly. The incorporation of AgNPs in the membranes did not adversely affect the membrane separation performance in NF and FO processes at low AgNPs incorporation levels. The FO performance of the silver nanocomposite membranes was better than or comparable to most NF-like FO membranes reported in the literature. In addition, the silver nanocomposite NF and FO membranes exhibited excellent antibacterial properties against both Gram-positive B. subtilis and Gram-negative E. coli. The results showed that the performances of the silver nanocomposite LbL membranes with AgNPs in membrane selective layers are highly dependent on silver incorporation in the membranes, which could be controlled by using different membrane synthesis routines and doping of AgNPs. Novel silver nanocomposite NF and FO membranes with enhanced water permeabilities and excellent antimicrobial properties were then fabricated by embedding the AgNPs in membrane substrates. The polyacrylonitrile silver nanocomposite membranes (PAN-Ag) were prepared using one-step phase inversion process and could be used as ultrafiltration (UF) membranes. With additional crosslinked layer-by-layer (xLbL) assembly on the UF substrates, xLbL-Ag nanocomposite membranes were obtained, which were applicable for both NF and FO operations. At the optimal concentration of AgNPs incorporation (0.02 wt.%), water permeability of PAN-Ag(0.02) UF membrane increased by 14.3 % compared with the AgNPs-free control; under the NF and FO testing conditions, corresponding water fluxes of NF/FO membrane increased by 10.1 % and 24.4 % respectively. In addition, the silver nanocomposite membranes exhibited excellent antibacterial performances. At the highest silver incorporation concentration of 0.10 wt.%, xLbL3.0-Ag(0.10) nanocomposite NF/FO membrane led to ~6 Log colony-forming units (CFU) reduction against Gram-positive B. subtilis and ~5 Log CFU reduction against Gram-negative E. coli.